Ratiometric fluorescence assay for L-Cysteine based on Fe-doped carbon dot nanozymes. (7th August 2020) - Lu, Changfang; Liu, Yao; Wen, Qin; Liu, Yang; Wang, Yanying; Rao, Hanbing; Shan, Zhi; Zhang, Wei; Wang, Xianxiang
Abstract: In this work, a ratiometric fluorescence method based on nanozyme was fabricated to determine L-Cysteine. Taking silkworm feces as a carbon source, together with Fe 3+, Fe-doped carbon dots (Fe-CDs) were synthesized through a hydrothermal method. Fe-CDs were able to oxidize the enzyme substrate o-phenylenediamine (OPD) to produce oxidized OPD (Ox-OPD) when H2 O2 coexisted with them. Based on the fluorescence property of Fe-CDs and Ox-OPD, a dual-emission system was built. Since L-Cysteine contains reductive thiols that can inhibit the production of Ox-OPD, the addition of L-Cysteine caused a decrease in the fluorescence intensity of Ox-OPD. The results showed that the ratio of fluorescence intensities at 450 and 560 nm (I450 /I560 ) varied linearly with the concentration of L-Cysteine in the range of 0.25–90 μ M and the limit of detection is as low as 0.047 μ M. Furthermore, using this ratiometric fluorescence system to determine L-Cysteine in serum and tap-water samples, average recoveries were evaluated to reach 98.75%–103.27% with the relative standard deviation of no more than 4.5%. Based on the fluorescence property and nanozyme-like activity, this work provides an inspiration to open a new horizon in using natural carbon source to synthesize CDs and for the application of CDs as a nanozyme.